Indexing and matching of polyphonic songs for query-by-singing system - LEUNG, Tat-Wan (Institutional Knowledge at Singapore Management University, 2004)
This paper investigates the issues in polyphonic popular song retrieval. The problems that we consider include singing voice extraction, melodic curve representation, and database indexing. Initially, polyphonic songs are decomposed into singing voices and instruments sounds in both time and frequency domains based on SVM and ICA. The extracted singing voices are represented as two melodic curves that model the statistical mean and neighborhood similarity of notes. To speed up the matching between songs and query, we further adopt proportional transportation distance to index the songs as vantage point trees. Encouraging results have been obtained through experiments.